Development of professional knowledge and identity of teachers in a tefl graduate programme through academic discourse socialization - Ahmadi, Parviz (2014)
This study investigatedhow five EFL in-service teachers in a graduate programme engaged in discourse socialization practices over the first year of the programme and how the collegial interactions nurtured the professional identity and knowledge development of these EFL teachers. Three research questions guided the study: 1. How does academic discourse socialization occur among in-service teachers in a TEFL graduate programme? 2. How does the participants’ engagement in discourse socialization practices focusing on oral coursework practices influence their professional knowledge? 3. How does the participants’ engagement in discourse socialization practices focusing on oral coursework practices influence their professional identity? The primary research tools used in this qualitative collective case study were individual interviews, group discussions and reflective writings of the participants. The interviews and group discussions were audio-recorded and transcribed in verbatim and a number of their writings were collected for analysis. The data were analysed both at a macro-level for any theme emerging from the interviews or discussions and at a micro-level for tracing epistemic markers in the data reflecting the perceptions and attitudes of the participants. The active participation of the participant teachers in discourse socialization practices facilitated learning in a collaborative learning community. The participants shared their personal practical experiences, scaffolded their peers and engaged with assigned academic texts. Their engagement in collegial discussions and with academic texts developed their professional knowledge in several aspects. Their awareness of pedagogical challenges was raised and they addressed their learners' needs and learning strategies in real classroom settings more effectively. The collegial interactions focused on the transfer of theories learned from the disciplinar textbooks to the pedagogical realities of the EFL educational settings. The engagement of the participant teachers in academic discourse socialization made them reconsider their pedagogical beliefs and practices. The participant EFL teachers reflected over their prior EFL teaching and learning beliefs and practices and shared them with their peers. In addition, the participants reconstructed and developed a relative expert identity as well as a critical identity over the status quo of their current EFL context. A number of implications for professional development of EFL teachers arise from this qualitative collective case study. A community of EFL teachers can provide them with support. Designing professional training programs that are likely to contribute to professional development of teachers through collegial interaction can be of great importanceas they may lead to reconsideration of their learning and teaching beliefs and practices.Guided supervision and more reflection in real settings can help teachers form the habit of reflection as life-long learning. Peer counselling services, skill-training under guided supervision, or any other form of support and scaffolding which provide motives for professional development should be encouraging.